2017
DOI: 10.4103/1658-354x.203057
|View full text |Cite
|
Sign up to set email alerts
|

A case report of suspected malignant hyperthermia where patient survived the episode

Abstract: Malignant hyperthermia is rare inherited disorder in our part of the world; there are only few cases reported in literature in India who were suspected of having this condition. The overall incidence of malignant hyperthermia during general anesthesia is estimated to range from 1: 5000 to 1: 50,000–100,000 and mortality rate is estimated to be <5% in the presence of standard care. In India, there is no center where in vitro halothane caffeine contraction test is performed to confirm diagnosis in suspected case… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…Constant muscle contraction causes a decrease in ATP levels and consequent difficulty in muscle relaxation, which explains the masseter rigidity presented by patients during the MH crisis [ 5 , 6 , 13 , 28 ]. The patient L.R.M.S.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Constant muscle contraction causes a decrease in ATP levels and consequent difficulty in muscle relaxation, which explains the masseter rigidity presented by patients during the MH crisis [ 5 , 6 , 13 , 28 ]. The patient L.R.M.S.…”
Section: Discussionmentioning
confidence: 99%
“…Late addition of dantrolene is also reported in intra- and postoperative MH cases with different results, and some were fatal, while others had no additional complications [ 2 , 45 , 53 , 54 ]. On the other hand, there were related intra- [ 28 , 55 ] and postoperative [ 54 ] MH cases in which dantrolene was not administrated due to non-availability of the drug in the hospital. Iqbal et al (2017) [ 28 ] reported the clinical signs and laboratory parameters altered by the MH crisis were reversed with internal (ice cold saline intravenously) and external (ice packs and cold towels over the body) cooling, and the patient had full recovery before being discharged.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A clinical grading system (CGS) can be used to assess the likelihood of MH based on a scoring system. According to this system, a patient with a score of >50 points has malignant hyperthermia [ 5 , 6 ]. The scoring system helps to identify acute crises in patients who have not been previously recognized as malignant hyperthermia-susceptible individuals or in situations where genetic or in vitro contracture testing is not possible.…”
Section: Introductionmentioning
confidence: 99%
“…However, patients have been shown to survive MH episodes even in the absence of dantrolene provided the diagnosis is considered early enough, and aggressive symptomatic treatment is carried out. [ 6 ] We were unable to confirm a definite diagnosis of MH because of unavailability of the “gold standard” confirmatory in vitro contracture test[ 4 ] however, pending future confirmatory studies it would be prudent to consider patients with CdCs as susceptible to MH and treated as such.…”
mentioning
confidence: 99%